EFFICACY OF ORAL AND INTRAMUSCULAR VITAMIB B12 IN EARLY RESPONSE AND PREFERENCES OF PATIENTS (CAHIERS MAGELLANES-NS, 2024)
Deficiency of vitamin B12 can be managed by oral substitution or intramuscular injection of vitamin B12. When different administration routes are present, the preference of patients should also be considered while treatment selection.  The main objective of our study was to assess the preferences of patients towards intramuscular injection or oral treatment of vitamin B12 supplementation, and to confirm the efficacy of both treatment options in patients.